Analisis Publik Tentang Brand Rucas Sebagai Fashion Lokal Limited Edition - Rahmadani, Aurellia Syahda; Hidayat, Muhammad Noor (Professional: Jurnal Komunikasi dan Administrasi Publik, 2025)
This study aims to analyze public perceptions of the local fashion brand Rucas,which adopts a limited edition concept as its core marketing strategy. Rucas has successfully built a strong and exclusive brand image by emphasizing product scarcity, a youth-relevant streetwear style, and inclusive social campaigns. This research employed a descriptive qualitative method using observation and interviews for data collection. The findings indicate that Rucas’ scarcity marketing strategy effectively fosters consumer loyalty, creates a unique shopping experience, and strengthens the brand's position in the local fashion market. Although the brand received positive reception, its cultural representation remains limited to visual elements. The study recommends that local brands further integrate cultural values into their products to enhance competitiveness and cultural identity.